Effects of Clostridium butyricum on Growth Performance, Gut Microbiota and Intestinal Barrier Function of Broilers - Li, Wenjia; Xu, Bin; Wang, Linyi; Sun, Quanyou; Deng, Wen; Wei, Fengxian; Ma, Huihui; Fu, Chen; Wang, Gaili; Li, Shaoyu (Frontiers in Microbiology, 2021)
The study was conducted to evaluate the effects of Clostridium butyricum dietary supplementation on the growth, antioxidant, immune response, gut microbiota and intestinal barrier function of broilers under high stocking density (HSD) stress. A total of 324 one-day-old Arbor Acres male broilers were randomly assigned to 3 treatment with 6 replicates, each replicate included 18 chickens (18 birds/m2). The experiment lasted 6 weeks. The 3 treatments were basal diet (CON), basal diet supplemented with 1 × 109 cfu/kg C. butyricum (CB), and basal diet supplemented with 10 mg/kg virginiamycin (ANT). The results showed that the body weight (BW) and average daily gain (ADG) of broilers in CB groups were significantly higher than those in control group (CON) in three periods (P < 0.05). The activities of total antioxidant capacity (T-AOC), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) in serum of CB group were significantly increased compared with control group and antibiotic group on 42 d (P < 0.05). At 42 d, the serum immunoglobulin M (IgM) and immunoglobulin G (IgG) level of CB group was significantly higher than control group. Compared with the control group, interleukin-1β (IL-1β) in C. butyricum group was significantly decreased in the starter and grower stages (P < 0.05), but there was no significant difference between the two treatment groups (P > 0.05). C. butyricum significantly decreased high stocking density-induced IL-1β and tumor necrosis factor-α (TNF-α) expression level in ileum of broilers at different stages. Additionally, C. butyricum could increase the expression of Claudin-1 and zonula occludens-1 (ZO-1) in intestinal tissue. Moreover, the C. butyricum significantly increased the Sobs and Shannon indices in CB group compared with in ANT group (P < 0.05), while the Ace index in CB group was significantly higher than that of CON group (P < 0.05). Furthermore, by using 16S rRNA gene sequencing, the proportion of Bacteroides in CB group was increased compared to the CON and ANT group at genera level. In conclusion, C. butyricum supplemented into feed could improve the growth performance and feed utilization of broilers by promoting immune, intestinal barrier function, and benefiting the cecal microflora.